Il ruolo dei consorzi per la valorizzazione del made in Italy nel mercato indiano - Francioni, Barbara; Musso, Fabio; Pagano, Alessandro (Piccola Impresa / Small Business, 2012)
This paper argues that export consortia should be re-assessed in terms of relevance and effectiveness, in the light of recent changes in international market competition. Therefore this paper aims to explore the role of export consortia to foster “Made in Italy” companies and products in emerging markets, attempting to highlight their limitations and opportunities. The empirical research is based on two case-studies of Italian export consortia active in the Indian market and promoting agrifood products. According to conducted research, the examined export consortia behaviour shows that little changes have emerged when compared to “traditional” approaches widely practiced in the past, even though it is clear that firms are increasingly aware about the possible role of export consortia in emerging markets.